2019
DOI: 10.3390/economies7030080
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Determinants of an Investor’s Decision in Unit Trust Investment

Abstract: Unit trust is a convenient way of investing and a sensible way to build one’s wealth in the medium term and subsequently in the long-term. Investment specialists will manage the investments and spread the risks through careful diversification. The basic nature of the unit trust is that it carries a low-level of risks and accordingly determines a lower level of returns compared to other financial instruments. There is a lack of research that empirically investigates the factors that influence an investor’s deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
17
0
3
Order By: Relevance
“…This is why Muslims with low risk attitudes feel more inclined to invest in Sharia instruments since they have no desire to experience more significant losses or risks. Previous studies also found that risk attitude had a positive influence on investment decisions (Annamalah et al, 2019;Gakhar, 2019;Kemp et al, 2018). However, the result from our study provides new evidence that Muslims' risk attitudes negatively influence their investment decisions in Sharia instruments.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…This is why Muslims with low risk attitudes feel more inclined to invest in Sharia instruments since they have no desire to experience more significant losses or risks. Previous studies also found that risk attitude had a positive influence on investment decisions (Annamalah et al, 2019;Gakhar, 2019;Kemp et al, 2018). However, the result from our study provides new evidence that Muslims' risk attitudes negatively influence their investment decisions in Sharia instruments.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have also shown that an individual's investment behaviour is associated with risk attitude (Annamalah et al, 2019;Gakhar, 2019;Kemp, Chan, Chen, & Helton, 2018). Raut, Das, and Kumar (2018) found attitude towards risk to be the most significant predictor for the investment intention of Indian investors.…”
Section: Previous Studymentioning
confidence: 93%
See 2 more Smart Citations
“…Investment behavior is influenced by internal and external factors [20]. The internal factors come from the personal characteristics of an individual investor.…”
Section: Introductionmentioning
confidence: 99%